Diabetic kidney disease macrophage cholesterol efflux: a revolution from metabolism to immune - Wang, Jinjin; Cai, Yi; Feng, Yuxi; Zhu, Qin (Frontiers in Endocrinology, 2025)
Diabetic kidney disease (DKD) is the most common microvascular complication of diabetes and a leading cause of end-stage renal disease (ESRD). Traditionally, its pathogenesis has been attributed to hyperglycemia-induced metabolic disturbances, glomerular hyperperfusion and hyperfiltration, activation of the renin–angiotensin–aldosterone system (RAAS), and oxidative stress. Recent evidence, however, indicates that chronic inflammation and immune dysregulation also play critical roles in DKD progression.Impaired macrophage cholesterol efflux (MCE) has emerged as a central pathogenic mechanism in DKD. Under hyperglycemic conditions, advanced glycation end-products (AGEs) suppress the LXR/PPARγ signaling pathway and downregulate downstream transporters ABCA1 and ABCG1, thereby reducing cholesterol efflux. This disruption promotes lipid accumulation and macrophage foam cell formation, leading to the sustained release of pro-inflammatory cytokines such as TNF-α, IL-1β, and MCP-1, which accelerate glomerulosclerosis and tubulointerstitial fibrosis. MCE dysfunction thus provides a mechanistic link bridging metabolic dysregulation and immune-mediated inflammation in DKD.Therapeutic strategies targeting MCE show promising potential. Pharmacological agents such as LXR/RXR agonists, PPARγ activators, sodium-glucose cotransporter 2(SGLT2) inhibitors, and glucagon-like peptide-1 receptor agonists(GLP-1RAs) enhance cholesterol transport, promote macrophage polarization toward the M2 anti-inflammatory phenotype, and ameliorate renal injury. In addition, natural bioactive compounds and nanodelivery systems can selectively modulate ABCA1/G1-mediated cholesterol efflux, attenuating lipid accumulation.In conclusion, this study highlights the pivotal role of macrophage cholesterol efflux in DKD pathogenesis beyond traditional metabolic factors and proposes novel MCE-targeted therapeutic strategies, offering new insights for the prevention and treatment of DKD.